Rugby coaches' perceptions of their in-competition role. Issue 1 (2nd January 2020) - Mouchet, Alain; Duffy, Pat
ABSTRACT: This study examined rugby coaches' perceptions concerning their in-competition role, when observing the game and managing player substitutions. Semi-structured interviews were conducted with seven coaches of French national teams. The data were analysed with a thematic qualitative analysis. The results revealed some similarities concerning the observation strategies, the significant cues for deciding substitutions, and shared procedures for player substitution management. There was evidence of a coaching "genre" shared by the coaches, which revealed a strong influence of the social and cultural context of French rugby. Nevertheless, the results also demonstrated important differences and the absence of a clear or common conceptual framework. This variety of statements revealed individual "coaching styles", adaptation to specific contexts, personal points of view and the importance of previous experiences in match coaching situations. The implications for the development of coaches are considered, with the potential for creating coaches' communities of practice and the use of reflection on subjective in-match experiences.